Etnobotânica da alimentação do Peixe-Boi da Amazônia (Trichechus inunguis, NATTERER 1883) do baixo Amazonas, Aamazonas e Terra Santa – PA - Vieira, Josué Goes (Brasil, 2023)
The objective of the present study was to gather information about the diet and eating habits of the Amazonian manatee through riverine ethnoknowledge and associate it with the species of aquatic macrophytes described in the scientific literature. The study was carried out in the Environmental Protection Area of Nhamundá in the municipality of Parintins-AM, also extending to the municipality of Terra Santa-PA, where dialogues were conducted in the form of informal conversations with potential fishermen of the species, revealed through of the “snowball” method. The interviewees listed a total of twelve varieties of aquatic macrophytes considered as part of the diet and have a common relationship with scientific research already carried out, just with simple direct observations and food traces left in the vegetation by the consumer in question. Therefore, the results reveal that Trichechus inunguis feeds on a wide variety of aquatic plant species and these species are recognized by ethnoknowledge, showing the importance of this type of knowledge for the scientific community.